Physical exercise program via telemonitoring during the COVID-19 pandemic for individuals with Parkinson's disease: intervention development study - Torriani-Pasin, Camila (2022)
BACKGROUND: To mitigate the COVID-19 pandemic, social isolation was needed. Since individuals with Parkinson’s disease (PD) have a high risk if catching the COVID-19, and physical exercise is one of the most effective treatments for this disease. In this scenario home-based exercise is a great solution to minimize losses by inactivity. AIM: To report the process of development of a remote physical exercise program based on a face-to-face physical exercise program. METHOD: We transform a one-hour-session-twice-a-week face-to-face program to a remote format keeping the objectives and structure. The sessions of the face-to-face program were structured by: warm-up, balance, aerobic capacity, resistance training, transference, and cool down. RESULTS: An asynchronous remote program was chosen to ensure that the participants would be able to perform the physical exercises with a caregiver or family member at home as safely as possible. The sessions were delivered by a single video with all 5 parts with prescriptions (time, sets, and repetitions), instructions about safety, and alternatives exercises. We create two questionnaires to investigate attendance, barriers, safety, and overall experience. CONCLUSION: This paper purposed an asynchronous program with a single video per session to initiate the remote program for individuals with PD, who already carried out a face-to-face program of physical exercise.